The effectiveness of monetary policy in steering money market rates during the financial crisis - Puriya Abbassi; Tobias Linzert (Deutsche Bundesbank, 2012)
The financial crisis has deeply affected money markets and thus, potentially, the proper functioning of the interest rate channel of monetary policy transmission. Therefore, we analyze the effectiveness of monetary policy in steering euro area money market rates looking at, first, the predictability of money market rates on the basis of monetary policy expectations, and second the impact of extraordinary central bank measures on money market rates. We find that during the crisis money market rates up to 12 months still respond to revisions in the expected path of future rates, even though to a lesser extent than before August 2007. We attribute part of the loss in monetary policy effectiveness to money market rates being driven by higher liquidity premia and increased uncertainty about future interest rates. Our results also indicate that the ECB's non-standard monetary policy measures as of October 2008 were effective in addressing the disruptions in the euro area money market. In fact, our estimates suggest that non-standard monetary policy measures helped to lower Euribor rates by more than 80 basis points. These findings show that central banks have effective tools at hand to conduct monetary policy in times of crises.
Keywords: E43; E52; E58; 330; Monetary transmission mechanism; Non-standard monetary policy measures; European Central Bank; Interbank money market